2014
DOI: 10.1186/s12862-014-0259-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genomes of the Baltic clam Macoma balthica(Bivalvia: Tellinidae): setting the stage for studying mito-nuclear incompatibilities

Abstract: BackgroundAllopatric divergence across lineages can lead to post-zygotic reproductive isolation upon secondary contact and disrupt coevolution between mitochondrial and nuclear genomes, promoting emergence of genetic incompatibilities. A previous FST scan on the transcriptome of the Baltic clam Macoma balthica highlighted several genes potentially involved in mito-nuclear incompatibilities (MNIs). As proteins involved in the mitochondrial oxidative phosphorylation (OXPHO) chain are prone to MNIs and can contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 66 publications
(116 reference statements)
0
25
0
Order By: Relevance
“…The typical 13 PCGs were identified in the four new mitogenomes analyzed here, including the atp8 gene, which had been reported as missing in several bivalve species [ 51 , 53 , 54 , 55 , 56 , 57 , 58 ], but subsequent analysis found its presence in several of them [ 48 , 50 , 52 , 59 , 60 , 61 , 62 ]. It was suggested that the short and variable length of this protein, along with its high variation in amino acid composition, might hinder the finding of this gene due to annotation difficulties [ 22 ].…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…The typical 13 PCGs were identified in the four new mitogenomes analyzed here, including the atp8 gene, which had been reported as missing in several bivalve species [ 51 , 53 , 54 , 55 , 56 , 57 , 58 ], but subsequent analysis found its presence in several of them [ 48 , 50 , 52 , 59 , 60 , 61 , 62 ]. It was suggested that the short and variable length of this protein, along with its high variation in amino acid composition, might hinder the finding of this gene due to annotation difficulties [ 22 ].…”
Section: Resultsmentioning
confidence: 77%
“…vittatus ). Although gene organization is known to vary extensively, even among species from the same genus [ 22 , 48 , 49 ], all four complete Donax mt genomes showed the same gene order and they are located on the “+” strand, likewise in Macoma balthica , other member of the Tellinoidea superfamily for which the whole mt genome is available [ 50 ]. The only difference was noted in the location of the longest NCR which, in M .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two F-type contigs (tig00000885 and tig00000888) were then merged. The quality of the mitogenome assembly was checked at each step of the pipeline (initial Canu assembly, Nanopolish polishing, Pilon polishing) by calculating the percent identity between our F-type unitigs and a published F-type mitogenome from the same sampling locality (KM373201) 43 using MUMmer 3.23 81 .…”
Section: Methodsmentioning
confidence: 99%